2018
DOI: 10.1017/s0950268818002455
|View full text |Cite
|
Sign up to set email alerts
|

Maternal infection during pregnancy and type 1 diabetes mellitus in offspring: a systematic review and meta-analysis

Abstract: Previous studies have demonstrated that type 1 diabetes mellitus (T1DM) could be triggered by an early childhood infection. Whether maternal infection during pregnancy is associated with T1DM in offspring is unknown. Therefore, we aimed to study the association using a systematic review and meta-analysis. Eighteen studies including 4304 cases and 25 846 participants were enrolled in this meta-analysis. Odds ratios (ORs) and 95% confidence intervals (CIs) were synthesised using random-effects models. Subgroup a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 42 publications
1
16
0
Order By: Relevance
“…Observational studies have found that increased paternal body mass index during pregnancy alters fetal cord blood methylation patterns, decreases neonatal IgM levels (32), is associated with delayed personal and social functioning in three-year-old children (33), increases the incidence of type II diabetes and insulin resistance (34), and is associated with the severity of obesity in childhood (35). Studies have found that obesity in the father during pregnancy alters birth weight (36)(37)(38) and increases the child's susceptibility to metabolic syndrome (36), subfertility (39), fatty liver (40), kidney disease (41), and hypertension (42) while reducing the child's cognitive function (43). It is widely believed that these factors have the potential to influence early embryonic and fetal growth and development, leading to the hypothesis that paternal obesity can influence pregnancy and child health outcomes long after pregnancy through epigenetic alterations.…”
Section: Discussionmentioning
confidence: 99%
“…Observational studies have found that increased paternal body mass index during pregnancy alters fetal cord blood methylation patterns, decreases neonatal IgM levels (32), is associated with delayed personal and social functioning in three-year-old children (33), increases the incidence of type II diabetes and insulin resistance (34), and is associated with the severity of obesity in childhood (35). Studies have found that obesity in the father during pregnancy alters birth weight (36)(37)(38) and increases the child's susceptibility to metabolic syndrome (36), subfertility (39), fatty liver (40), kidney disease (41), and hypertension (42) while reducing the child's cognitive function (43). It is widely believed that these factors have the potential to influence early embryonic and fetal growth and development, leading to the hypothesis that paternal obesity can influence pregnancy and child health outcomes long after pregnancy through epigenetic alterations.…”
Section: Discussionmentioning
confidence: 99%
“…As an insulin-dependent type of diabetes, T1DM is relatively harmful to human health [20]. Autoimmune-mediated pancreatic b-cell destruction is one of the pivotal pathophysiological mechanisms of T1DM, leading to severe insulin deficiency [21,22].…”
Section: Discussionmentioning
confidence: 99%
“…Viral infections in pregnancy, specifically by enteroviruses [17], have been associated with type 1 diabetes in the offspring, though the mechanisms are complex and evidence circumstantial [18, 19]. Two recent systematic reviews and meta-analyses identified a potentially causative link between maternal viral infections in pregnancy and type 1 diabetes in the offspring [20, 21]. Interestingly, monocytes from mothers with gestational diabetes show a proinflammatory profile [22], which can also be induced in fetal monocytes of mothers infected with hepatitis B virus [22].…”
Section: Intrauterine Exposures and Programming Of Type 2 Diabetes Anmentioning
confidence: 99%